Participation Tax Rates in Finland, Earnedincome Tax Credit Investigated - Kotamäki Mauri (Aboa Centre for Economics (ACE), 2016)
Previous estimates on participation tax rates (PTRs) are reviewed and new, updated PTR estimates of the Finnish case are provided with 2013 data. The results indicate that there has been an increase in the average PTR in Finland after 2011. The sensitivity of PTR calculations is tested in order to understand the dynamics behind the results. This is something that is lacking in the earlier literature. The contribution of different parts of the social security system to the level of PTR is calculated. Furthermore, a recent reform, the increase of Earned-income Tax Credit (EITC), is evaluated in an ex-ante manner. It could be possible to utilize the underlined methodology when evaluating and designing policy reforms. First, the reform's effect on average participation tax rate is calculated. Second, the obtained result with respect to average PTR is plugged into a search theoretic general equilibrium model, and an employment effect is estimated. Also a more traditional "partial equilibrium" effect is calculated. The EITC reform, that costs (in static terms) exteuro450 million, lowers the average PTR by 1 pp., which is calculated to induce a 0.6-0.8 % increase in the number of employed using 0.25 elasticity of labor supply.
Keywords: J20; J22; H20; 330; Participation tax rates; Earned-income Tax Credit; social security; general equilibrium modeling